0127 Comparison Of Oral And Video Debriefing And Its Effect On Knowledge Acquisition Following Simulation-based Learning. (1st November 2014) - Thorley-Dickinson, Victoria; Purva, Makani; Dieckmann, Peter; Kasfiki, Eirini; Omer, Rasha
Abstract : Background: Learning from simulation takes place to a large extent in debriefing, 1 however there is still sparse knowledge about the advantages and disadvantages of debriefing methods. 2 Two common forms are video-assisted and oral only debriefing. We have set out to determine if there is increased knowledge acquisition for candidates undergoing video, rather than oral debriefing. Methodolgy: Qualified second year doctors were randomised to a training day with either oral or video feedback. Candidates underwent a 15 min emergency clinical scenario followed by 30 min feedback. The candidates completed 30 MCQs to establish baseline knowledge of treating common clinical emergency scenarios, and repeated these after simulation training. From projected statistical analysis we will have a sample size of 135 candidates. Results: Interim results for 97 candidate's pre and post course MCQs are available at this time. Both groups have demonstrated a statistically significant increase in their pre and post test percentage score (oral 79.9% vs 85.9%, p =< 0.0001, video 80.0% vs 84.9%, p =< 0.0001). There is no statistically significant difference in the post test percentage scores between oral and video groups (85.9% vs 84.9%, p = 0.2576). Potential impact: There is an improvement of knowledge from the simulation training day, but we have not demonstrated a difference between video to oral debriefing. Simulation training aims to teach human factors abilities which MCQs are unable to measure. We will also be undertaking 3 month interviews to analyse candidate's understanding of human factors and how they relate to their work. This will allow us to investigate further the role that video feedback can play in simulation-based learning. References: Issenberg SB, McGaghie WC, Petrusa ER, et al . Features and uses of high-fidelity medical simulations that lead to effective learning: a BEME systematic review. Med Teach 2005;27(1):10–28 Raemer et al . Reseach regarding debriefing as part of the learning process. Simul Healthc 2011;6(Suppl):S52–7